10.1016/s0029-7437(08)70194-0 (CrossRef Listing of Deleted DOIs, 2000)
Aim To compare clinical outcomes and patient-reported outcome measures (PROMs) of palatal donor-site healing following the use of an absorbable gelatine sponge, a chitosan sponge or an injectable platelet-rich fibrin (i-PRF)-enriched chitosan sponge after free gingival graft harvesting. Materials and methods In this three-arm randomised controlled clinical study, a total of 68 patients were allocated to three groups: i-PRF + chitosan (n = 22), chitosan (n = 23) and gelatine sponge (control; n = 23). The primary outcome was the palatal early healing index (PEHI). Secondary outcomes included PROMs, namely postoperative pain, burning sensation and changes in dietary habits, which were evaluated using a visual analogue scale (VAS) at postoperative days 7, 14, 28 and 56. Bleeding and painkiller consumption were recorded daily. Colour match was assessed using VAS. Results Both chitosan-containing groups showed significantly higher PEHI scores, particularly on days 14 and 28, than the control group (p < 0.001). At Day 14, the median PEHI scores were 8.0 (Q1-Q3: 7.0-8.0; 95% CI for the median: 7.0-8.0), 8.0 (Q1-Q3: 8.0-9.0; 95% CI: 8.0-9.0) and 9.0 (Q1-Q3:8.0-9.0; 95% CI: 8.0-9.0) in the control, chitosan and i-PRF-enriched chitosan groups, respectively. The i-PRF + chitosan group showed significantly lower pain and burning sensation during early healing and less changes on dietary habits on days 3 and 7 compared with the other groups (p < 0.05). Bleeding and painkiller consumption were similar among groups (p > 0.05). Both test groups showed significantly better colour match than the control group at days 14, 28 and 56 (p < 0.001). Conclusion Within the limitations of the present study, chitosan improved early palatal wound healing, while the addition of i-PRF enhanced patient comfort. Both chitosan-containing approaches resulted in improved colour match compared with control. Nevertheless, further studies incorporating histological and biomolecular assessments of wound healing are needed to confirm these findings.